Metabolic alterations in the tumor microenvironment and their role in oncogenesis. (1st August 2020) - Eisenberg, Lihie; Eisenberg-Bord, Michal; Eisenberg-Lerner, Avital; Sagi-Eisenberg, Ronit
Abstract: Metabolic reprogramming is a characteristic feature of both cancer cells and their neighbouring cells in the tumor microenvironment (TME). The latter include stroma fibroblasts and adipocytes, that respectively differentiate to become cancer associated fibroblasts (CAFs) and cancer associated adipocytes (CAAs), and infiltrated immune cells, that collaborate with the stromal cells to provide the tumor a pro-tumorigenic niche. Here we discuss the association between the reprogramming of glucose metabolism in the TME and oncogenic signaling and its reflection in the non-canonical functions of metabolic enzymes. We also discuss the non-canonical actions of oncometabolites and the contribution to oncogenesis of external metabolites that accumulate in the TME as result of crosstalk between the tumor and the TME. Special emphasis is given in this regard to lysophosphatidic acid (LPA) and adenosine, two powerful metabolites, the concentrations of which rise in the TME due to altered metabolism of the tumor and its surrounding cells, allowing their action as external signals. Highlights: Metabolic reprogramming is a characteristic feature of cancer cells and their neighbouring cells. Mitochondria dysfunction in cancer is due to mitochondria mutations or mitochondria adaptation to oncogenic signaling. Non-canonical functions of metabolic enzymes contribute to oncogenesis. Non-canonical functions of metabolites that accumulate in cancer contribute to oncogenesis. External metabolites that accumulate in the tumor microenvironment generate a pro-tumorigenic niche.